Nation, culture, and identity: writing Gaelic Britain from 1639–1715 - Black, Thomas S. G. (2020)
The purpose of the thesis is to examine the literary representations of the national and cultural identities of the Gaels in Scotland and Ireland from 1639-1715. This thesis demonstrates that Gaelic identities were already significantly divergent between Scotland and Ireland at the outset of this time-frame, and that this continued throughout the period notwithstanding common causes such as royalism and Jacobitism. As this thesis explores, this divergence is largely due to the very different internal politics and ethnic dynamics of early modern Scotland and Ireland. Nevertheless, although this thesis argues that a greater identification with the nations of Scotland or Ireland is evident on both sides of the channel, this is often in tandem with a partially incongruent, yet enduring, identification with a cultural Gaelic identity. The disjuncture between Scottish and Irish national identities and a Gaelic identity which had as its cultural heritage a space and history that exceeded that of just Scotland or just Ireland, is one of the key tensions this thesis explores. In Ireland, Gaelic identity was partially reconstructed into a patriotic and religious vision of Irishness in which the Gaels were part of a uniquely Catholic history. In Scotland, Gaelic identity retained its keen sense of difference from the Lowland Scots – though this was not necessarily antagonistic – and for many it also became bound up into a dynastic loyalty to the House of Stuart and to the Kingdom of Scotland. These discourses were refracted through the complex of literary cultures and practices of the early modern archipelago, and this thesis demonstrates that a study of the different genres, linguistic traditions, and mediums taken together is necessary to capture the manifold and subtle representations of Gaelic identities during this period.